Analisis Penerapan Aplikasi Lamikro pada Laporan Keuangan UMKM Laundry Kecamatan Kulim Kota Pekanbaru - R. Annisa Amelia Putri; Mariaty Ibrahim (Lembaga Pengembangan Kinerja Dosen, 2025)
This study analyzes the implementation of the Lamikro application (Micro Business Accounting Report) in the financial statements of laundry SMEs in Kulim District, Pekanbaru. The objective of this research is to assess the effectiveness of the Lamikro application in enhancing the quality of record-keeping and financial report preparation, as well as its impact on business profitability. The research employs a descriptive quantitative method, involving six months of observation and in-depth interviews with three laundry SMEs: Prigamas Laundry, DiLaundry, and Nisa Laundry. The findings indicate that Lamikro significantly improves the efficiency and accuracy of financial report preparation, reducing the time required from 8-15 hours to just 1-3 hours. Adaptation to the application varied, with DiLaundry being the fastest and Nisa Laundry the slowest. Analysis of the Net Profit Margin (NPM) reveals an increase in profitability for all three SMEs: Prigamas Laundry (from 69.05% to 70.34%), DiLaundry (from 47.46% to 55.92%), and Nisa Laundry (from 48.14% to 49.21%). It is concluded that Lamikro effectively enhances the quality of financial reports and profitability of laundry SMEs, influenced by digital literacy and managerial commitment.